'Savoy Truffle': Love, Lust and Longing in a Box of Chocolates - Neill, L; Hemmington, N (Ingenta, 2018)
This article re-reads The Beatles’ song, ‘Savoy Truffle’, not as an ode to Eric Clapton’s rotting teeth and chocolate consumption, but rather as a thinly veiled rock music metaphor reflecting the triptych love relationship between its composer, George Harrison, his wife, Pattie Boyd, and her lover and later husband, Eric Clapton. Re-reading ‘Savoy Truffle’ provides a valuable insight into the intricacies of how popular rock music communicates constructs of love within metaphor and how The Beatles integrated multiple meanings into lyrics conveying love and its contention. Such multiplicity aids explanations exploring the band’s extraordinary popularity by providing a socio-temporal insight into an extra-ordinary time: the 1960s. In re-reading ‘Savoy Truffle’, this article contextualizes the multiplicity of love itself within an exploration of the passion within lust, the longing of desire and the satisfaction of having the desired object. The desired object was Pattie Boyd, who Harrison projected within a box of ‘Good News’ chocolates.
Keywords: Eric Clapton; George Harrison; Pattie Boyd; The Beatles; Triptych Love; ‘Savoy Truffle’